Clinical classification and early therapy for COVID-19. Cases reported from Hospital de Emergencias Villa el Salvador, Lima-Peru - Mendoza-Ticona, Alberto (2020)
The disease caused by SARS-CoV-2 is a pandemic characterized for being highly contagious and lethal in groups at risk. In less than three months, mankind had to fight against this virus without knowing its pathogenicity and therapy. We present the experience with five cases seen in the Hospital de Emergencias Villa el Salvador in Lima, Peru, and we emphasize the importance of the clinical classification of the disease in four stages: mild, moderate, severe, and critical. We reviewed the current antiviral, immunomodulatory, and antithrombotic therapy approaches. Antiviral therapy using hydroxichloroquine and azithromycin led to favorable outcomes in four cases, particularly when it was early instituted. Nonetheless, its efficacy is still controversial and results from randomized clinical trials are eagerly awaited. Meanwhile, its use during the early phases of mild or moderate disease should be maintained.